Taxonomic and distributional notes on Spongilla-flies (Neuroptera: Sisyridae) from Southeastern Brazil with first interactive key to the species of the country - Assmar, Alice Carvalho; Salles, Frederico Falcão (Zootaxa, 2017)
Based on adults collected from Espírito Santo, Southeastern Brazil, we present the first reports of Sisyridae from the state, expanding the known distributional range of five species of Climacia McLachlan and Sisyra Burmeister. Adults were collected throughout two basins, Rio Doce and São Mateus, and its tributaries in the north of the state with Pennsylvania light trap. Two species are reported for the first time from Southeastern Brazil. Furthermore, we describe the male of Climacia basalis Banks and compare it with the male of its junior synonym, C. desordenata Monserrat. In addition, traditional and interactive keys are proposed for the identification of all the species of Sisyridae reported from Brazil.